Integrating models of disability in special education law for children with disabilities in Malaysia - Othman, Muhammad Fikri; Rahmat, Nur Ezan; Abdul Aziz, Norazlina; Abdul Hak, Nora; Kamarudin, Diyana (Anka Publishers, 2022)
Article 26 of the Universal Declaration of Human Rights (UDHR) provides everyone has the right to education. The term 'everyone' includes children with disabilities, and the government has a legal responsibility to provide equal educational opportunities to all children. There are two popular models of disability in the Disability Studies: The Social Model and Medical Model of Disabilities. Both models are distinct from each other. In Malaysia, the Malaysian Education Blueprint 2013-2025 provides education for children with disabilities through special education needs. However, since there are inconsistencies in the definition of persons with disabilities, no specific law for special education for children with disabilities, and non-integrated data by relevant agencies in Malaysia, children with disabilities' educational rights are not protected. Therefore, to protect their educational rights, both models of disability will be analysed to suggest whether the rights can be efficiently protected by integrating the Social Model and Medical Model of Disabilities in special education law for children with disabilities in Malaysia. This paper aims to explore the current laws related to special education for children with disabilities in Malaysia and examine the Social Model and Medical Model of Disabilities’ inadequacy in protecting their educational rights. Besides, this paper aims to suggest the integration between the Social Model and Medical Model of Disabilities to efficiently protect the educational rights of children with disabilities in Malaysia. A doctrinal analysis is adopted in this paper where textbooks, journal articles, and encyclopedias related to special education for children with disabilities are analysed.